AGRONOMY IMPROVING THE FERTILITY OF ALLUVIAL SOILS IN THE HAZELNUT PLANTATION USING GREEN MANURES (Conferencea, 2023)
The study refers to the selection of measures to increase the fertility of the alluvial soils of the georgian region - samegrelo in the hazelnut plantation, which is built in the training-trial farm of akaki tsereteli state university.